2022
DOI: 10.3390/biomedicines10020444
|View full text |Cite
|
Sign up to set email alerts
|

Uremic Toxin Lanthionine Induces Endothelial Cell Mineralization In Vitro

Abstract: Vascular calcification (VC) is a pathological event caused by the unusual deposition of minerals in the vascular system, representing the leading cause of cardiovascular mortality in chronic kidney disease (CKD). In CKD, the deregulation of calcium and phosphate metabolism, along with the effect of several uremic toxins, act as key processes conveying altered mineralization. In this work, we tested the ability of lanthionine, a novel uremic toxin, to promote calcification in human endothelial cell cultures (Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 81 publications
(94 reference statements)
0
6
0
Order By: Relevance
“…et al explored the effects of lanthionine, a pending uremic toxin, on the cardiovascular system of zebrafish larvae [ 217 ]. Lanthionine is a non-proteinogenic amino acid generated as a side-product of the action of trans-sulfuration enzymes in hydrogen sulfide (H 2 S) biosynthesis, and it has been demonstrated as a potential uremic toxin with several untoward effects [ 211 , 212 , 213 , 218 ]. Lanthionine has been detected in two orders of magnitude concentrations higher in hemodialysis patients compared to normal subjects, where this compound is almost undetectable in circulation [ 202 , 203 ].…”
Section: Zebrafish As a Model To Study Uremic Cardiotoxicitymentioning
confidence: 99%
“…et al explored the effects of lanthionine, a pending uremic toxin, on the cardiovascular system of zebrafish larvae [ 217 ]. Lanthionine is a non-proteinogenic amino acid generated as a side-product of the action of trans-sulfuration enzymes in hydrogen sulfide (H 2 S) biosynthesis, and it has been demonstrated as a potential uremic toxin with several untoward effects [ 211 , 212 , 213 , 218 ]. Lanthionine has been detected in two orders of magnitude concentrations higher in hemodialysis patients compared to normal subjects, where this compound is almost undetectable in circulation [ 202 , 203 ].…”
Section: Zebrafish As a Model To Study Uremic Cardiotoxicitymentioning
confidence: 99%
“…Several mechanisms are involved in the progression of CKD toward ESRD, which are still not entirely clear. For example, the accumulation of uremic toxins, and especially sulfur compounds such as homocysteine and lanthionine, are among the leading culprits affecting cardiovascular risk [ 68 ]. Many clinical manifestations are related to CKD.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…These overall manifestations are known as «chronic kidney disease-bone mineral disease» (CKD-BMD). CKD-MBD is strictly related to an impaired production of calcitriol, the hormone derived from vitamin D [ 68 , 69 , 70 ]. CKD is also associated with gastrointestinal problems, (hiccoughs, anorexia, gastritis, gastrointestinal bleeding, alteration in intestinal barrier permeability), which are also related to dysbiosis.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In line with the widespread belief that endothelial dysfunction is the earliest stage of atherosclerosis, Coppola et al [ 26 ] published an in vitro study in human EC cultures (Ea.hy926) to explore the role of vascular calcification as the leading cause of cardiovascular mortality in chronic kidney disease (CKD). In particular, the authors demonstrated that the uremic toxin lanthionine, generated as a side-product of the trans-sulphuration process, is able to modify endothelial homeostasis at a concentration similar to that usually documented in CKD patients, with the expression of specific markers involved in the mineralization process.…”
mentioning
confidence: 99%